Acclimation of 2‐chlorophenol‐biodegrading activated sludge and microbial community analysis. (26th March 2019) - Sun, Zhirong; Zhang, Jinwei; Yang, Jie; Li, Jiangyang; Wang, Jianguang; Hu, Xiang
Abstract: Using glucose as cosubstrate, activated sludge that could effectively biodegrade 40 mg/L 2‐chlorophenol was successfully domesticated in sequencing batch reactors. To acclimate the sludge, 2‐chlorophenol was increased stepwise from 0 to 40 mg/L. High‐throughput sequencing revealed that the microbial community richness increased during the first 5 days of acclimation to 5 mg/L 2‐chlorophenol and then decreased after another 20 days as 2‐chlorophenol was increased. The original sludge obtained from a water resource recovery facility had the highest microbial diversity. As the acclimation continued further, community richness and diversity both increased, but they decreased again, significantly, when 2‐chlorophenol reached 40 mg/L. Saccharibacteria_norank, Bacillus, Saprospiraceae_uncultured, and Lactococcus were the dominant bacteria. Bacillus and Pseudomonas were the main known chlorophenol‐degrading bacteria. WCHB1‐60_norank, Tetrasphaera, Comamonadaceae_unclassified, and Haliangium showed poor tolerance to 2‐chlorophenol. Higher bacterial tolerance to chlorophenols does not mean higher degrading capability. The degradation of chlorophenols was not positively correlated with the detected abundance of known 2‐chlorophenol‐degrading bacteria. Practitioner points: Activated sludge that could effectively biodegrade 40 mg/L 2‐chlorophenol was successfully domesticated using glucose as cosubstrate in sequencing batch reactors. Saccharibacteria_norank, Bacillus, Saprospiraceae_uncultured, and Lactococcus were the dominant bacteria. Bacillus and Pseudomonas were the main known chlorophenol‐degrading bacteria detected in this study. The degrading capability and tolerance of bacteria to chlorophenols were relatively independent and the degradation of chlorophenols may be the synergistic effect of various bacteria.